What makes a people according to Israel's wisdom literature? ἔθνος and ἔθνη in proverbs, Wisdom of Sirach and Wisdom of Solomon - Wischmeyer, Oda (What Makes a People?, 2023)
This paper examines concepts of ethnicity in the older and younger wisdom writings of Israel. A line extends from a purely descriptive political perception of the constellation "Israel-surrounding peoples" in the older wisdom to a more essentialist understanding of Israel as the people of God in the Wisdom of Solomon.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Ancient Jewish sapiential literature; Concepts of ethnicity; Ethnicity; Ethnos